Nursing students’ satisfaction of the clinical learning environment: a research study - Papastavrou, Evridiki (BMC Nurs, 2016)
BACKGROUND: The acquisition of quality clinical experience within a supportive and pedagogically adjusted clinical learning environment is a significant concern for educational institutions. The quality of clinical learning usually reflects the quality of the curriculum structure. The assessment of the clinical settings as learning environment is a significant concern within the contemporary nursing education. The nursing students’ satisfaction is considered as an important factor of such assessment, contributing to any potential reforms in order to optimize the learning activities and achievements within clinical settings. The aim of the study was to investigate nursing students’ satisfaction of the clinical settings as learning environments. METHOD: A quantitative descriptive, correlational design was used. A sample of 463 undergraduate nursing students from the three universities in Cyprus were participated. Data were collected using the Clinical Learning Environment, Supervision and Nurse Teacher (CLES + T). RESULTS: Nursing students were highly satisfied with the clinical learning environment and their satisfaction has been positively related to all clinical learning environment constructs namely the pedagogical atmosphere, the Ward Manager’s leadership style, the premises of Nursing in the ward, the supervisory relationship (mentor) and the role of the Nurse Teacher (p < 0.001). Students who had a named mentor reported more satisfied with the supervisory relationship. The frequency of meetings among the students and the mentors increased the students’ satisfaction with the clinical learning environment. It was also revealed that 1st year students were found to be more satisfied than the students in other years. CONCLUSION: The supervisory relationship was evaluated by the students as the most influential factor in their satisfaction with the clinical learning environment. Student’s acceptance within the nursing team and a well-documented individual nursing care is also related with students’ satisfaction. The pedagogical atmosphere is considered pivotal, with reference to students’ learning activities and competent development within the clinical setting. Therefore, satisfaction could be used as an important contributing factor towards the development of clinical learning environments in order to satisfy the needs and expectations of students. The value of the development of an organized mentorship system is illustrated in the study.